DAMPAK PENGEMBANGAN DESA WISATA MEKARSARI TERHADAP EKONOMI MASYARAKAT LOKAL DI KECAMATAN NARMADA - I Ketut Bagus Artana Sukarta; Muhamad Sayuti; Mimi Cahayani (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
This study aims to determine the impact of developing a tourism village on changes in the area of Mekarasari Village; and to determine the impact of the development of a tourist village on the local community's economy in Mekarsari Village, Narmada District, West Lombok. This research was conducted in Mekarsari Village, precisely in Mekarsari Tourism Village, Narmada District, West Lombok. The type of research used in this study uses a qualitative approach method with data collection techniques used, namely data collection through observation, interviews, and documentation. Data collection through interview activities. The number of informants in the interviews was 30 informants who came from the people of Mekarsari Village, Narmada District. The results of the study show that: 1) The development of the Mekarsari tourism village has a positive impact on the Mekarsari Village area and the local community's economy in the form of community income and opportunities to work and do business; 2) The development of the Mekarsari tourist village for the local community's economy can be seen from the increase in income earned by the village and the local community itself. As well as the existence of open opportunities for work and business for the village community in Mekarsari Village.